The influence of halal practices on organizational performance among food industries (SMEs) in Malaysia - Baharudin Othman; Sharifudin Md. Shaarani; Arsiah Bahron; Nurul Hudani Md. Nawi (Jabatan Kemajuan Islam Malaysia (JAKIM), 2019)
The aim of this study is to investigate the influence of halal practices on organizational performance among the halal food industries (Small and Medium Enterprises — SMEs) in Malaysia. In this study, four key elements have been identified as performance predictors which are; halal and thoyyib, internal process, halal assurance, and staff. A cross-sectional study design has been adopted in this study through quantitative methods using closed-ended questions. Questionnaires were distributed to the halal food industry in Malaysia, and 172 of them are usable for analysis at an organizational level. Respondents who participated in this study are internal committee members specially appointed for halal control management within the organisation. Data were analyzed by using SPSS version 21. Descriptive analysis showed that the level of halal practices and the performance of the halal food industry in Malaysia were positive. In addition, the inference test results proved that there is a significant correlation between all the variables studied. However, based on the regression analysis, the halal and thoyyib; and halal assurance dimensions majorly influence the performance of the organization as compared to internal dimensions of the process and staff. This research gives the implications toward government, industry and consumers.